Penerapan Kinerja Karyawan BBPI Saat Pandemi Covid-19 - Andhi Supriyadi; Catur Yulianto (STIE PGRI Dewantara Jombang, 2021)
Corona virus (covid-19) is a virus which transmits disease through touch. This can spread in small droplets which come from nose or mouth when coughing or sneezing. Government takes many policies on various aspects of life at the economic sector, education, tourism, health and even activities of life in the community. Work from Home is one of the government’s policy, Work from home is a term of working remotely, more precisely working from home. Some factors that affect performance by work from home are personality, organizational communication, and work facilities. Data results of the questionnaire are use in this study by sample data collection techniques of 30 people from 127 populations. SPSS analysis tool, used as analysis technique in the study, which multiple linear regression by conducting validity tests, reliability testing, correlation analysis of regression analysis, coefficient of confirmation and testing of the hypothesis. Results showed that the Adjusted RSquare (coefficient of determination) on 0.986. This concludes that the independent variables (personality, organizational communication and facilities) can explain 98.6% of the dependent variable (employee performance). And the rest of 1.4% (100% - 98.6%) are explaining other independent variables that not proposed in this research.